2019
DOI: 10.1113/ep087451
|View full text |Cite
|
Sign up to set email alerts
|

Computational multivariate modelling of electrical activity of the porcine uterus during spontaneous and hormone‐induced oestrus

Abstract: New Findings What is the central question of this study?Does oestrous cycle synchronization influence myoelectrical activity of porcine myometrium? What is the main finding and its importance?Exogenous hormones used to synchronize oestrus in pigs altered myoelectrical activity, which was effectively modelled. Higher‐order multivariate statistic modelling provided evidence of similar activity in both types of oestrus, but a larger order of EMG signals during induced oestrus. Higher‐order statistical analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…In vivo, ex-vivo and in-virtro data have been used for developing model and/or model validation. Data were always recorded noninvasively from a living person or sometimes invasively from animals so as to obtain useful signals with less noise [47], [48]. Subsequently, the studies on uterus modeling at different levels are reviewed, from cellular level, at which the generation of action potential and/or force is described.…”
Section: Uterus Modeling At Different Levelsmentioning
confidence: 99%
See 2 more Smart Citations
“…In vivo, ex-vivo and in-virtro data have been used for developing model and/or model validation. Data were always recorded noninvasively from a living person or sometimes invasively from animals so as to obtain useful signals with less noise [47], [48]. Subsequently, the studies on uterus modeling at different levels are reviewed, from cellular level, at which the generation of action potential and/or force is described.…”
Section: Uterus Modeling At Different Levelsmentioning
confidence: 99%
“…Although most models have been developed for contributing to the human beings, animal models were also taken into consideration with in vivo invasive recording which contains less noise and produces additional crucial information about uterine activity [32], [47]. Domino et al considered porcine uterus as a reference model for preclinical study and indicated its high applicability [47], [48]. Wu et al performed MRI scan and surgery on Karahdin sheep, whose abdomen size is similar as that of humans.…”
Section: Model At Organ Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the analogical approach in [241] authors have applied higher order culuants tensors to analyse features of the EMG signal of the estrus cycle in pigs. Here, in contrary to the classical statistical approach, the higher order cumulants tensors model shows evidences of large EMG activity during induced estrus.…”
Section: Cumulants In Machine Learningmentioning
confidence: 99%
“…This is in contrary to the spontaneous estrus. Authors of [241] concludes, that higher order cumulants tensors are indicator revealing a probabilistic model of dynamic changes in the myometrial electrical activity as a result of positive and negative feedback of the reproductive hormones.…”
Section: Cumulants In Machine Learningmentioning
confidence: 99%